Pengaruh Terapi Murottal Al Qurâ€™an terhadap Kualitas Tidur Lansia di Unit Rehabilitasi Sosial Dewanata Cilacap - Oktora, Sasongko Priyo Dwi; Purnawan, Iwan (Jurusan Keperawatan FIKES UNSOED, 2016)
One of Elderly problems is a bad quality of sleep. Sircadian Rhythme change in elderly is caused by the decreation of serotonin production. The murottal Al QurÃ¢â‚¬â„¢an Therapy use a rhythmical and harmonious melody so that it can stimulates serotonin productions. So it is one of therapy that probably solve elderly bad quality of sleep. The study aim to identify the effect of murottal Al QurÃ¢â‚¬â„¢an therapy on elderly quality of sleep. This study used quasi experiment design. Simple random sampling applied to 40 respondents that divided into two groups, intervention and control group. Quality of sleep was measured with PSQI. Inclusion criteria were good hearing respondent, 60 till 80 years old, and wanted to follow this research. Exclusion criteria were mental health diseae, smooking and used sleep medications.Statistic analysis with paired t test showed that there was a significant difference between before and after gived murottal Al QurÃ¢â‚¬â„¢an therapy in intervention group (p value = 0,000Ã‚Â : ÃŽÂ± = 5%). But the other side there was no significant difference between before and after observation in control group (p value = 0,083).. It conclouded Murottal Al QurÃ¢â‚¬â„¢an therapy is effective to increase eldery quality of sleep.